2019
DOI: 10.1111/jar.12639
|View full text |Cite
|
Sign up to set email alerts
|

Improving healthcare access for older adults with intellectual disability: What are the needs?

Abstract: This qualitative study was carried out in Spain with the aim of identifying the changes that the health system should make to improve healthcare access for older adults with intellectual disability. Three hundred and sixty‐nine family members and professionals expressed their opinion on how healthcare access could be improved. Participants responded to two open‐ended questions included in a general survey about the health status of older individuals with intellectual disability. Most informants were women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The objectives that underpinned this work represent a considerable advance in the understanding of self‐determination in people with intellectual disabilities over 45 years old. From this age, according to several authors (Dykens, 2013; Lim et al, 2018; Navas et al, 2019), the symptoms associated with the natural ageing process become more noticeable in this group. The development of self‐determination in late adulthood is an issue barely addressed in the international literature and is nonexistent in the Latin American context.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The objectives that underpinned this work represent a considerable advance in the understanding of self‐determination in people with intellectual disabilities over 45 years old. From this age, according to several authors (Dykens, 2013; Lim et al, 2018; Navas et al, 2019), the symptoms associated with the natural ageing process become more noticeable in this group. The development of self‐determination in late adulthood is an issue barely addressed in the international literature and is nonexistent in the Latin American context.…”
Section: Discussionmentioning
confidence: 88%
“…Some authors (Tang et al, 2020) cite natural cognitive impairment as an explanatory factor for this trend. According to these studies, people with intellectual disabilities may have premature ageing processes (from age 45) generally accompanied by mental health disorders or emotional problems that make it difficult to perform self‐determination skills (Navas et al, 2019). Indeed, one of the main findings of this research points to the presence of mental health disorders among participants could be a possible conditioning factor of self‐determination and self‐regulation processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, research has indicated that individuals with ID are three times more likely than the general population to die from causes that could have been easily avoided [66]. Furthermore, the scientific literature has reported that older adults with ID encounter different barriers that hinder access to appropriate medical care, among which the absence of healthcare protocols focused on their aging process stands out [38,67,68]. There is therefore an urgent need to develop preventive healthcare plans to improve the health-related quality of life of older persons with ID.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them are related to the disability itself, like the existence of communication difficulties that complicate the diagnosis [37], but there are also contextual factors that could contribute to a higher prevalence of chronic health conditions within this group. Outstanding among the latter are difficulties to access healthcare services [38], high poverty rates [39] that are related to poorer nutrition [40], residential care settings where physical inactivity might prevail [41], high rates of polypharmacy [42], or a lack of healthcare standards for people with ID in general, and for those who are aging in particular [43]. Such factors, among others, can have a negative impact not only on the incidence of health-related problems, but also on their progression and severity through the last stage of people with ID's lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Restricted access to healthcare of ID represents a serious social limitation ( 7 , 8 ). Various factors contribute to a limited access to healthcare for ID: stigmatization ( 9 ), comorbidities and difficulty in communication ( 10 ), misconceptions and negative attitudes toward ID ( 11 ), lack of knowledge or attention on part of healthcare providers ( 11 , 12 ), insufficient research activities ( 13 ), lack of integration of disability-specific content in medical curricula ( 14 ), difficulties regarding the transport of ID to medical facilities and associated high costs ( 7 , 11 ), insufficient flexibility of the medical care system that frequently overlooks specific needs of ID ( 12 ), poverty ( 11 ), barriers in access to medical facilities ( 15 ), and a lack of integration of the voices of ID in service design ( 8 ).…”
Section: Introductionmentioning
confidence: 99%